La improcedencia de los acuerdos conciliatorios en los delitos de tránsito cuando el resultado sea daños permanentes e irreversibles - Escobar Naranjo, Segundo Arnulfo (2016)
Traffic accidents have become a serious health problem, causing the deaths and disability that generates sometimes the victims of these events. Causing a social problem, the physical and psychological damage suffered by these people and their subsequent reintegration into society, under different conditions to those experienced previously. The number of traffic accidents in our country grows increasingly, which have left as a result wounded with permanent injuries and despite this the victim and the offender choose to reach a settlement in order to avoid prosecution. But that Article 663 paragraph 2 of the Code Integral Penal and Article 5 of conciliation rules prohibit conciliation when the result of a traffic offense is death, there is a loophole that directly affects the repair of victims left with permanent damage. It is for this reason that the thesis presents a proposed amendment to that article where it is excluded from the reconciliation to traffic offenses that result in permanent and irreversible damage, thus victims will be repaired in full. The conceptual, legal, doctrinal foundation and comparative law, allowed me to get a comprehensive and accurate picture of the invalidity of the settlements in traffic offenses knowledge when the result is permanent and irreversible damage. To achieve the results of research surveys and interviews with practitioners on the illegality of settlements in traffic offenses were made as the result is permanent and irreversible damage. These results were analyzed using descriptive and inferential statistical methods, which contributed to the verification of the objectives and the testing of the hypothesis